Study on the infection characteristics and pathogenesis of duck circovirus 1 in Cherry Valley meat ducks - Hanqing Li; Guige Xu; Hui Yan; Lei Bei; Mingrui Zhao; Ruihua Zhang; Yu Meng; Yanli Zhu; Liangmeng Wei; Zhijing Xie; Shijin Jiang (Poultry Science)
Duck circovirus (DuCV) infected multiple breeds of ducks and was widespread in duck factories worldwide. Infected ducks exhibited feathering disorder, growth retardation and immunosuppression, which lead to secondary infection with other pathogens easily. But till now, there has been little research on the study of DuCV due to the absence of appropriate cultural measures. This study developed an animal model to investigate the pathogenesis of DuCV-1 in vivo by infecting 84 one-day-old Cherry Valley meat ducklings. At 1, 3, 7, 14, 21, 28 and 35 days post-infection (DPI), six Cherry Valley meat ducks were randomly chosen to detect some indexes. The results showed that ducks infected with DuCV-1 exhibited depression, feather disorders and gained weight slowly. DuCV-1 was detected in serum, cloacal swabs, and throat swabs at 1 DPI and sustained during the experimental period. The contents of calcium, phosphorus and lymphocytes decreased while alanine aminotransferase and total bilirubin increased in the serum of sick ducks. DuCV-1 was detectable in all organs and caused multiple local lesions. The virus was initially detected in the liver and the organ with the highest viral titer was the thymus. Besides, immune organ indexes were significantly decreased. These results demonstrated that DuCV-1 could be transmitted horizontally and cause infection persistently. It possesses broad tissue tropism, damaging immune organs and potentially inducing immune suppression. This study could provide references for future research on the pathogenic mechanism of DuCV.